The Labour Market Impacts of Obesity, Smoking, Alcohol Use and Related Chronic Diseases - Devaux, Marion (OECD Publishing, 2015)
This paper examines the labour market impacts of lifestyle risk factors and associated chronic diseases, in terms of employment opportunities, wages, productivity, sick leave, early retirement and receipt of disability benefits. It provides a review of the evidence of the labour market outcomes of key risk factors (obesity, smoking and hazardous drinking) and of a number of related chronic diseases, along with findings from new analyses conducted on data from a selection of OECD countries. Overall, the evidence suggests that chronic diseases and associated risk factors have potentially large detrimental labour market impacts, but with mixed findings in some areas. Obesity and smoking clearly impair employment prospects, wages and labour productivity. Cardiovascular diseases and diabetes have negative impacts on employment prospects and wages, and diabetes, cancer and arthritis lower labour productivity. Alcohol use, cancer, high blood pressure and arthritis have mixed effects on employment and wages, and are not always linked with increased sickness absence (e.g. cardiovascular diseases and high blood pressure). Finally, this paper stresses the importance of these findings for the economy at large, and supports the use of carefully designed chronic disease prevention strategies targeting people at higher risk of adverse labour market outcomes, which may lead to substantial gains in economic production through a healthier and more productive workforce
Keywords: Social Issues/Migration/Health